Epithelial debridement and Bowman's layer polishing for visually significant epithelial irregularity and recurrent corneal erosions - Aldave, Anthony J.; Mohd. Kamal, Khairidzan; Vo, Rosalind C. (Lippincot William @ Wilkins, 2009)
PURPOSE: To report the utility of epithelial debridement and diamond burr polishing of Bowman's layer (ED + DBP) in the management of recurrent corneal erosions and visually significant epithelial irregularity associated with epithelial basement membrane dystrophy (EBMD).